Shortcomings [videorecording (DVD)] - Tomine, Adrian, 1974-; Min, Justin H., 1990-; Cola, Sherry, 1989-; Maki, Ally, 1986-; Gevinson, Tavi, 1996-; Ryan, Debby, 1993-; Mizuno, Sonoya; Hsu, Stephanie (Actor); Chieng, Ronny; Batalon, Jacob, 1996-; Simons, Timothy; Tomine, Adrian, 1974- (Sony Pictures Home Entertainment, 2023)
Friends navigate interpersonal relationships and cross the country in search of an ideal connection.